Pregnancy-related acute kidney injury: A narrative review - Abhilasha Soni; Archana Bajpayee; Manish Chaturvedy; Rajesh Jhorawat; Nitin K Bajpai (Wolters Kluwer -Medknow Publications, 2023)
An acute renal insult during pregnancy increases the chances of acquiring chronic kidney disease in future by many folds; thus, the management of renal disease in pregnancy becomes increasingly important to the nephrologist. In depth understanding of normal physiological changes during pregnancy is crucial in diagnostic evaluation and management. Acute insult to kidney can happen any time during pregnancy and even in the postpartum period. The incidence of acute kidney injury during pregnancy has decreased over time due to improvement in health sector and various policies promoting woman health. Women with pre-existing renal disorders face various challenges in pregnancy including increased risk of disease progression, the potential teratogenicity of medications and various fetal implications like preterm delivery or intra-uterine death. Pre-existing autoimmune disease or diabetes mellitus requires interdisciplinary team management for favorable maternal and fetal outcome. This review highlights the physiologic changes in pregnancy, different spectrum of kidney diseases related to pregnancy and their management.